PENGARUH EKSPEKTASI KARIER, BIAYA PENDIDIKAN, DAN MINAT MEMILIH PROGRAM STUDI TERHADAP KEPUTUSAN MEMILIH PROGRAM STUDI PENDIDIKAN EKONOMI - Dyastari Cahya Regita; Arintoko; Kholifaturrohmah, Ramita (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
This study aims to analyze the influence of career expectations, tuition fees, and interest on students' decisions in selecting the Economics Education Study Program at Jenderal Soedirman University. This research provides practical benefits for various parties. For researchers, it broadens their horizons and hones their scientific skills. For study programs, the results can provide input for development. For prospective and new students, this research helps them design a well-thought-out educational and career plan and strengthens their confidence in choosing a study program based on their interests, career expectations, and tuition fees. This study used a quantitative approach with 128 respondents from the 2023 and 2024 student intakes selected using cluster random sampling. The data analysis techniques used in this study included multiple linear regression analysis, the coefficient of determination, the F-test, and the t-test. The results indicate that career expectations, tuition fees, and interest positively influence study program selection decisions. These findings suggest that increasing the attractiveness of study programs can be achieved through active promotion on social media and official websites, as well as providing transparent information regarding tuition fees and scholarship opportunities to support prospective students' considerations. Keywords: Career Expectations, Education Costs, Interest in Choosing a Study Program, Decision to Choose a Study Program.